Aqueous extracts of Elsholtzia ciliata and Hovenia dulcis ameliorate loperamide-induced constipation in mice by promoting intestinal peristalsis and barrier function and the abundance of intestinal beneficial bacteria - Wu, Junnan; Xin, Qilei; Wang, Shuo; Zhang, Xu; Jiang, Chunping (Frontiers in Microbiology, 2025)
ObjectiveThe aims of the present study were to determine the efficacy of edible traditional Chinese medicines (ETCMs) in treating constipation, verify their laxative effects, and conduct preliminary investigations into their mechanisms of action.MethodsICR mice were treated with loperamide to induce constipation, and various fecal parameters, including fecal volume, water content, and intestinal transport function, were measured in these constipation model mice to screen for ETCMs with laxative properties. The mechanism of action was preliminarily explored by examining changes in the intestinal mucosal structure, protein expression levels, and alterations in intestinal flora composition.ResultsIn ICR mice with loperamide-induced constipation, Elsholtzia ciliata aqueous extract (ECAE) and Hovenia dulcis aqueous extract (HDAE) significantly ameliorated constipation symptoms, mitigated colonic pathological tissue damage, significantly increased the expression levels of proteins associated with the promotion of intestinal peristalsis [Stem Cell Factor Receptor (c-Kit) and Stem Cell Factor (SCF)] and the maintenance of the intestinal barrier [Zonula Occludens-1 (ZO-l), Occludin and Claudin-l], and promoted beneficial intestinal bacterial colonization.ConclusionECAE and HDAE ameliorated constipation in mice, and their mechanism of action may be related to the increased abundance of intestinal bacteria such as Turicibacter, Olsenella, and Odoribacter, which contribute to higher butyrate production. This increase in butyric acid reduces inflammation, improves intestinal barrier function, and increases the abundance of beneficial intestinal bacteria.